Evasion and Immuno-Endocrine Regulation in Parasite Infection: Two Sides of the Same Coin in Chagas Disease? - Morrot, Alexandre; Villar, Silvina R.; González, Florencia B.; Pérez, Ana R. (Frontiers in Microbiology, 2016)
Chagas disease is a serious illness caused by the protozoan parasite Trypanosoma cruzi. Nearly 30% of chronically infected people develop cardiac, digestive or mixed alterations, suggesting a broad range of host-parasite interactions that finally impact upon chronic disease outcome. The ability of T. cruzi to persist and cause pathology seems to depend on diverse factors like T. cruzi strains and the infective load, the route of infection, the release of immunomodulatory or virulence factors, the parasite capacity of avoid protective immune response, the strength and type of host defence mechanisms and the genetic background of the host. In this context, the host-parasite interaction is subject to a constant neuro-endocrine regulation, and as the infection proceeds can lead to a broad range of outcomes, from elimination of the pathogen to its continued persistence in the host with the consequent induction of pathology. In particular, neuro-endocrine balance, effector and regulatory T cells are key points where the host can take advantage to improve their defence mechanisms, or contrarily may be exploited by parasites to survive and persist. In this context, T. cruzi evasion strategies and host defence mechanisms can be envisioned as two sides from the same coin at the complex host-parasite relationship influencing parasite persistence and different outcomes observed in Chagas disease. Understanding on how T. cruzi evade innate and adaptive immune response and how parasite persistence might be favoured by immuno-neuro-endocrine regulation will provide important clues to better dissect mechanisms underlying the pathophysiology of Chagas disease.